Research of a trusted execution environment module for multiple platforms - Qian-ying ZHANG; Shi-jun ZHAO; Wei FENG; Yu QIN; Deng-guo FENG (Tongxin xuebao)
The current TPM,MTM and other trusted computing modules don’t take into account the variety of platforms and the update of the inside algorithms,protocols and functions.A hardware trusted execution environment module (TEEM) architecture,which uses ARM TrustZone technology to build a trusted computing module running in a secure isolated environment is designed.Proposed module not only supports variety of platforms,but also has strong mobility and portability.Moreover,it allows configuring and updating functions and algorithms of the module flexibly.A prototype system is implemented and its performance is tested.By analyzing the security of the system and the measurement results,it is shown that TEEM provides users with a safe,stable,efficient trusted execution environment.